ON (3,6) AND (4,6) - FULLERENE CAYLEY GRAPHS - ASHRAFI, Ali Reza; LOGHMAN, Amir; MOGHARRAB, Mojgan (Studia Universitatis Babeș-Bolyai Chemia, 2016)
An (r, s)-fullerene graph is a planar 3-regular graph with only Cr and Cs faces, where Cn denotes a cycle of length n. In this paper, the (3,6)-fullerene Cayley graphs constructed from finite groups are classified. A characterization of (4,6)-fullerene Cayley graphs is also presented.